Konflik Etnis di Ambon dan Sambas: Suatu Tijauan Sosiologis - Syarif Alqadrie (Antropologi Indonesia, 1999)
The ethnic conflict in Ambon and Sambas are the result of the same casual factors. The ambivalent and unfair treatment by the armed forces and the police, and the absence of law enforcement, were factors that led to the emergence of these conflicts. Numerous crimes and violent actions (by gangster and preman) Took place. The local people - the Dayak and Malay community of Sambas, and the Ambon communities (both, Moslem and Christian, and also the Bugis, Buton, and Makassar) - took harsh measures without regard for the law. They did so since they could no longer trust the law, the armed forces and the police... [...] in the last part of this article, the author proposes three steps for the solution to the conflicts in both places: the shorts medium, and long term solutions.